Role of Coping Styles, Locus of Control, and Emotional intelligence in Predicting Social Adjustment of Veterans with Post-Traumatic Stress Disorder - N. Mikaeili; S. Einy; R. Taghavy (Afarand Scholarly Publishing Institute, 2018)
Aims: Social adjustment is one of the important structures of mental health, in which the identification of influential factors is of high importance. The aim of this study was to investigate the role of coping styles, locus of control, and emotional intelligence in predicting social adjustment of veterans with post-traumatic stress disorder (PTSD). Instrument and Methods: In the descriptive correlational study, 120 veterans with PTSD hospitalized and treated in Isar Psychiatric Hospital in Ardabil selected based on the available sampling method, were studied in 2017. The data were collected, using Bell adjustment inventory, Lazarus and Folkman coping styles questionnaire, Rotter's locus of control scale, and Schutte et al. emotional intelligence scale. The data were analyzed by SPSS 21 software, using Pearson correlation coefficient test and stepwise regression analysis. Findings: Social adjustment of veterans with PTSD had a positive and significant relationship with emotional intelligence, internal locus of control, and problem-focused coping style and had a negative and significant relationship with external locus of control and emotion-focused coping style (p<0.001). Also, 78% of variance of social adjustment scores in the veterans with PTSD were predicted by coping styles, locus of control, and emotional intelligence (p<0.001) and the most predictive power was for emotional intelligence. Conclusion: Problem-focused coping styles, internal locus of control, and high emotional intelligence predict high social adjustment in veterans with PTSD.